2020
DOI: 10.1088/1755-1315/454/1/012071
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of bovine semen using egg yolk substituted with extract guava in water from yellow coconut on the semen quality and fertility of Bali cattle

Abstract: The present study used the ratio of 80% coconut water and 11 - 20% egg yolk substitution with extract guava ranged from 4 to 9% in order to determine the quality and fertility of Bali cattle storaged at 50C. This study used a complete factorial design with two factors and six treatments. The first factor was coconut water and egg yolk substituted with extract guava extender at different ratio consisted of 6 treatments. They were: (1) T0 (control) = 80% coconut water + 20% egg yolk without extract guava; (2) T1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…A previous study has shown that the use of guava extract can maintain intact plasma membrane and intact acrosome hood of Bali bull spermatozoa during storage for six days (Marawali et al, 2020).However, there are relatively few reports regardeing the use of guava products as an antioxidant source for chicken spermatozoa.Therefore, this study was conducted to evaluate the effects of adding various levels of guava juice in the Andromed diluent on the semen quality of indigenous chicken during storage upto 90 minutes at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has shown that the use of guava extract can maintain intact plasma membrane and intact acrosome hood of Bali bull spermatozoa during storage for six days (Marawali et al, 2020).However, there are relatively few reports regardeing the use of guava products as an antioxidant source for chicken spermatozoa.Therefore, this study was conducted to evaluate the effects of adding various levels of guava juice in the Andromed diluent on the semen quality of indigenous chicken during storage upto 90 minutes at room temperature.…”
Section: Introductionmentioning
confidence: 99%